Mobile Drip Irrigation for Water Limited Crop Production: Initial Results - J. Aguilar; T. Oker; I. Kisekka (Kansas Agricultural Experiment Station Research Reports, 2019)
The farmers within the Ogallala aquifer desire to extend the usable life of this aquifer despite experiencing diminishing well capacities, thus the quest for more efficient irrigation application technologies. Mobile drip irrigation (MDI), which integrates drip lines onto a mechanical irrigation system such as a center pivot, has attracted their attention lately. The concept is that by applying water along crop rows, it was hypothesized that MDI could eliminate water losses due to spray droplet evaporation, wind drift, and reduce soil evaporation due to limited surface wetting especially before canopy closure. A study was conducted with the following objectives: 1) compare soil water evaporation under MDI and in-canopy spray nozzles (low elevation spray application (LESA)); 2) evaluate soil water redistribution under MDI at 60-inch drip line lateral spacing; and 3) compare corn grain yield, and water productivity under MDI and LESA at two well capacities (300 and 600 gpm). The experimental design was randomized complete block with four replications and two treatments (MDI and LESA). Nozzle performance was evaluated using the Spot-on flow measurement device. Soil water evaporation was measured using 4-inch mini-lysimeters placed between corn rows. The effect of a 60-inch lateral spacing on soil water redistribution was measured using neutron attenuation to a depth of 8 feet. Corn yield was determined from harvesting two 40-foot corn rows in the center of each plot. Measured and design nozzle flow rates were similar indicating the irrigation system was performing as designed. Results indicate that soil water evaporation was lower under MDI compared to LESA by an average of 35%. Soil water was greatest at the mid-point between two drip line laterals spaced 60 inches apart at a depth of approximately 20–24 inches. These results indicate drip line spacing of 60 inches is adequate for silt loam soils of southwest Kansas. The effect of irrigation application method (MDI versus spray nozzles [LESA]) on yield at high (600 gpm) and low (300 gpm) well capacities was not statistically significant at the 5% level (P>0.05). The effect of application method on water productivity and irrigation water use efficiency was also not significant. The lack of significant differences in yield could be attributed to the above normal rainfall received during the 2015 growing season (18 inches from May to September). However, it is worth noting that the effect of application method on end-of-season soil water was statistically significant under low well capacity (300 gpm) with mobile drip irrigation having more soil water compared to spray nozzles.
Keywords: mobile drip irrigation; MDI; center pivot; crop; irrigation